Diasporas - Beine, Michel; Docquier, Frederic; Ozden, Caglar (2012)
Migration flows are shaped by a complex combination of self-selection and out-selection mechanisms, both of which are affected by the presence of a diaspora abroad. In this paper, we analyze how existing diasporas (the stock of people born in a country and living in another one) affect the size and human-capital structure of current bilateral migration flows. Our analysis exploits a bilateral data set on international migration by educational attainment from 195 countries to 30 OECD countries in 1990 and 2000. Based on simple micro-foundations and controlling for various determinants of migration, we found that diasporas increase migration flows and lower their average educational level. Interestingly, diasporas explain majority of the variability of migration flows and selection. This suggests that, without changing the generosity of family reunion programs, education-based selection rules are likely to have moderate impact. Our results are highly robust to the econometric techniques, accounting for the large proportion of zeros and endogeneity problems.